2020
DOI: 10.1093/ckj/sfaa127
|View full text |Cite
|
Sign up to set email alerts
|

Preventive strategies for acute kidney injury in cancer patients

Abstract: Acute kidney injury (AKI) is a common complication of cancer that occurs in up to 50% of neoplastic patients during the natural history of their disease; furthermore, it has a huge impact on key outcomes such as overall prognosis, length of hospitalization and costs. AKI in cancer patients has different causes, either patient-, tumour- or treatment-related. Patient-related risk factors for AKI are the same as in the general population, whereas tumour-related risk factors are represented by compression, obstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 79 publications
0
21
0
1
Order By: Relevance
“…We hypothesize the reason might be due to a complication of cancer or the treatment. Patients with cancer are at higher risk of developing infections, sepsis, tumor lysis syndrome, and drug-associated toxicity that significantly increase the risk of developing AKI [25][26][27]. Other reported factors associated with AKI were heart failure, atrial fibrillation, hematological disorders, and massive/severe PE [7,10,13].…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize the reason might be due to a complication of cancer or the treatment. Patients with cancer are at higher risk of developing infections, sepsis, tumor lysis syndrome, and drug-associated toxicity that significantly increase the risk of developing AKI [25][26][27]. Other reported factors associated with AKI were heart failure, atrial fibrillation, hematological disorders, and massive/severe PE [7,10,13].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth to note that certain cancers like leukemias, lymphomas, multiple myelomas (MM) and renal cell cancer (RCC) in both human and veterinary patients are related with the higher risk of AKI development, not only due to the accompanying kidney involvement, but also due to the hypotension, sepsis, administration of different anti-fungal and anti-bacterial agents, cytotoxic or immunosuppressive drugs and even hematopoietic stem cell transplantation (HSCT) and tumor lysis syndrome (TLS). The appropriate scheme of cancer treatment seems to be an ideal preventive strategy from AKI development [70].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Another study from China showed that there were 1,418 malignancy-related AKI in 7,604 AKI patients according to KDIGO criteria (25). Both patient-specific and cancer-related risk factors including age, co-morbid conditions, chemotherapy, surgery and radiotherapy increase the risk of AKI in cancer patients (26). Critically ill cancer patients with AKI had increased mortality compared patients without AKI (27).…”
Section: Question 4 How Is the Prognosis Of Critically Ill Cancer Patients With Acute Kidney Injury?mentioning
confidence: 99%